DNA plasmid coding for Phlebotomus sergenti salivary protein PsSP9, a member of the SP15 family of proteins, protects against Leishmania tropica. - Elham Gholami; Fabiano Oliveira; Tahereh Taheri; Negar Seyed; Safoora Gharibzadeh; Nasim Gholami; Amir Mizbani; Fatemeh Zali; Sima Habibzadeh; Daniel Omid Bakhadj; Claudio Meneses; Kambiz Kamyab-Hesari; et al. (Public Library of Science (PLoS), 2019)
Background The vector-borne disease leishmaniasis is transmitted to humans by infected female sand flies, which transmits Leishmania parasites together with saliva during blood feeding. In Iran, cutaneous leishmaniasis (CL) is caused by Leishmania (L.) major and L. tropica, and their main vectors are Phlebotomus (Ph.) papatasi and Ph. sergenti, respectively. Previous studies have demonstrated that mice immunized with the salivary gland homogenate (SGH) of Ph. papatasi or subjected to bites from uninfected sand flies are protected against L. major infection. Methods and results In this work we tested the immune response in BALB/c mice to 14 different plasmids coding for the most abundant salivary proteins of Ph. sergenti. The plasmid coding for the salivary protein PsSP9 induced a DTH response in the presence of a significant increase of IFN-γ expression in draining lymph nodes (dLN) as compared to control plasmid and no detectable PsSP9 antibody response. Animals immunized with whole Ph. sergenti SGH developed only a saliva-specific antibody response and no DTH response. Mice immunized with whole Ph. sergenti saliva and challenged intradermally with L. tropica plus Ph. sergenti SGH in their ears, exhibited no protective effect. In contrast, PsSP9-immunized mice showed protection against L. tropica infection resulting in a reduction in nodule size, disease burden and parasite burden compared to controls. Two months post infection, protection was associated with a significant increase in the ratio of IFN-γ to IL-5 expression in the dLN compared to controls. Conclusion This study demonstrates that while immunity to the whole Ph. sergenti saliva does not induce a protective response against cutaneous leishmaniasis in BALB/c mice, PsSP9, a member of the PpSP15 family of Ph. sergenti salivary proteins, provides protection against L. tropica infection. These results suggest that this family of proteins in Ph. sergenti, Ph. duboscqi and Ph. papatasi may have similar immunogenic and protective properties against different Leishmania species. Indeed, this anti-saliva immunity may act as an adjuvant to accelerate the cell-mediated immune response to co-administered Leishmania antigens, or even cause the activation of infected macrophages to remove parasites more efficiently. These findings highlight the idea of applying arthropod saliva components in vaccination approaches for diseases caused by vector-borne pathogens.